AN EXPLORATION OF OPPRESSION: JOOTHAN AS A DALIT AUTOBIOGRAPHY - Magadum, Parappa; V.F. Nagannawar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article analyses Omprakash Valmiki's Joothan as a pivotal text in Dalit literature, focussing on its depiction of caste oppression, resistance, and the transformational influence of education. Joothan, a memoir of Valmiki's existence as a "untouchable" in India, reveals the persistent humiliations and adversities faced by the Dalit group. The title of the narrative, signifying "leftover scraps," functions as a potent metaphor for the dehumanisation of Dalits, highlighting the social and psychological ramifications of caste discrimination. Valmiki utilises a candid and unembellished literary style to emphasise themes of exclusion, resistance, and self-assertion in relaying his personal experiences. This article contextualises Joothan within the socio-historical framework of Dalit literature, examining its alignment with Dr. B.R. Ambedkar's principles of empowerment via education and self-respect. Valmiki’s narrative is both a chronicle of adversity and a monument to the fortitude and endurance of marginalised populations. Through the reclamation of his voice and identity, Valmiki confronts the established caste hierarchies and asserts the acceptance of the humanity and dignity of the Dalit people.